The Influence of the Teams Games Tournament (TGT) Learning Model Assisted by Wordwall on Motivation and Mathematics Learning Outcomes in the Society 5.0 Era - Darmawati, Darmawati; Arifin, Sartika; Hakim, Fauziah (Mandalika Mathematics and Educations Journal, 2025)
The development of technology in the era of society 5.0 requires education to produce human resources that are adaptive to technology. Mathematics as a fundamental science is still considered difficult and monotonous, thus requiring innovative learning strategies. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model assisted by Wordwall on students’ motivation and mathematics learning outcomes in grade XI at SMA Negeri 1 Bambang in the era of society 5.0. This research employed a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of an experimental class (XI Health Specialization, 23 students) and a control class (XI Informatics Specialization, 28 students). The research instruments used were a learning motivation questionnaire, a learning outcome test, and an observation sheet. Data were analyzed descriptively and inferentially using a t-test. The results showed a significant increase in the experimental class, where students’ learning motivation rose from 62.74 to 74.22 and learning outcomes improved from 45.04 to 72.30, while the control class showed minimal improvement. Hypothesis testing (sig. 0.000 < 0.05) confirmed that the TGT model assisted by Wordwall had a significant effect on students’ motivation and mathematics learning outcomes. Therefore, this model is proven effective in improving the quality of mathematics learning in the society 5.0 era.